(untitled) (Південний архів (історичні науки), 2026)
The aim of this study is to examine the intellectual activities of local government representatives in southern Ukraine during the 19th and early 20th centuries as a means for shaping public opinion. Scientific novelty. This article analyzes the activities of local government in southern Ukraine from a social perspective. Within the framework of this study, the historical process is examined not as the evolution of political institutions, but through the lens of the intellectual history of the activities of local government representatives in the 19th and early 20th centuries. Research methodology. Methodologically, this study is based on a human-centered approach, which was applied to analyze the individual of municipal employees through the lens of the diversity of their experiences, allowing for the exploration of self-government as a personal phenomenon. The human-centered approach is complemented by a local research method, which makes it possible to highlight the uniqueness and individuality of each local government unit and outline its spatial configuration at the social level, thereby shedding light on the cultural dimension. Within the framework of local history, the concept of microhistory is employed, which helped explain the work of specific historical figures in unconventional contexts. The study focuses primarily on analyzing and reinterpreting the experience of self-governing institutions in southern Ukraine. Conclusions. The findings indicate that the intellectual work of local government deputies in southern Ukraine deserves attention, as it embodies the experience of the practical implementation of municipal work at the local level. Their work, for the most part, is not purely academic but applied. They convey information and draw upon sources that, unfortunately, have not survived to the present day. Various aspects of practical self-governing activities are conveyed and characterized through the prism of the authors’ personal perceptions of the period under study.